2008
DOI: 10.1016/j.mrgentox.2008.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome aberrations in mouse embryos and fetuses produced by assisted reproductive technology

Abstract: The occurrence of structural chromosome aberrations in mouse one-cell embryos produced by intracytoplasmic sperm injection (ICSI) with mature spermatozoa was dependent on the type of sperm incubation medium and sperm incubation time. When cauda epididymal spermatozoa were used following incubation in bicarbonate-buffered TYH medium for 0 h (no incubation) and 0.5 h, the chromosome aberration rates (6.9% and 7.4%, respectively) in the resultant embryos were significantly higher than that (2.3%) in the IVF embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…The incidence of structural chromosomal aberrations in the control group was also generally higher in zygotes produced by ICSI (Table 3) than in those produced by in vitro fertilization (Table 2). This is consistent with the report that ICSI performed using testicular spermatozoa is accompanied by increased chromosome damage (Tateno, 2008).…”
Section: Chromosome Analysis Of Zygotessupporting
confidence: 93%
“…The incidence of structural chromosomal aberrations in the control group was also generally higher in zygotes produced by ICSI (Table 3) than in those produced by in vitro fertilization (Table 2). This is consistent with the report that ICSI performed using testicular spermatozoa is accompanied by increased chromosome damage (Tateno, 2008).…”
Section: Chromosome Analysis Of Zygotessupporting
confidence: 93%
“…The incidence of chromosomal abnormalities obtained in this study using IVP of embryos by ICSI (14.28%) was higher than reported for human where approximately 5% of children born by ICSI carry a risk of chromosomal abnormalities (Bonduelle et al 1999). This result may support previous studies in mouse (Tateno 2008) and humans (Bonduelle et al 1999), but the present data seem be too small to conclude a high prevalence of chromosome anomaly in swine ICSI. Further studies must be carried out to confirm these preliminary observations.…”
Section: Discussionsupporting
confidence: 84%
“…1999). This result may support previous studies in mouse (Tateno 2008) and humans (Bonduelle et al. 1999), but the present data seem be too small to conclude a high prevalence of chromosome anomaly in swine ICSI.…”
Section: Discussionsupporting
confidence: 81%
“…Marchetti et al [40] suggested that mouse embryos with a small number (less than four) of paternally transmitted chromosome aberrations experienced problems in later embryonic stages. Mouse zygotes with structural chromosome aberrations generated spontaneously via ICSI can develop into live offspring carrying chromosome alterations [41,42].…”
Section: Importance Of Chromosomal (Dna) Integrity In Freeze-dried Spmentioning
confidence: 99%